“ШАҲРИЁР” ДОСТОНИНИНГ ЭРТАК ШАКЛИДАГИ АСАРЛАР БИЛАН БОҒЛИҚЛИГИ - Кенесбаева, Ш.К. (SCIENCE and SOCIETY, 2022)
The article analyzes the fact that fairy-tale epics such as "Shahriyor", "Shiyryn Sheker", "Qanshayym", "Munlyq - Zarlyq" are a new aesthetic system, not in terms of genre, but in terms of creativity. The history of creation and performance of the epic "Shahriyor" and other Karakalpak fairy-tale epics is also analyzed.
Keywords: "Shahriyor" epic; Kurbanbay Jirov; O.Kojurov; K.Maksetov; J.Khoshniyazov; epics with a fairy-tale plot; epics "Shiyryn Sheker"; "Qanshayym"; "Munlyq - Zarlyq"; "Tulym biy"